2.56 Gbps CML transceiver for data concentrator ASIC. (1st March 2022) - Atkin, E.; Serazetdinov, A.
Abstract: 2.56 Gbps CMOS CML-transceiver is presented. The key feature of the design is capability of working with specific inductive load and transmitting data to the remote room about 1 meter away from the experimentation vicinity. Some radiation tolerance techniques used are shown. Testing methodology is briefly described, and concepts in test board realization are provided. The transceiver was designed as an interface part of the data concentrator ASIC, intended for the frontend electronics of the time-projection chamber of the MPD experiment at NICA nuclotron.